1989
DOI: 10.1111/j.1471-4159.1989.tb09179.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Protective Enzymes Against Peroxidation in the Central and Peripheral Nervous System of Control and Dysmyelinating Mutant Mice

Abstract: The activities of peroxide-detoxifying enzymes such as superoxide dismutase (SOD), glutathione peroxidase, glutathione reductase, and catalase were measured in the nervous system of neurological dysmyelinating mutants: quaking (Qk), shiverer (Shi), and trembler (Tr) mice. Cu/Zn-SOD activity was higher in the cerebellum of Qk and Shi mice (by 53% and 106%, respectively) in comparison with controls, but it was the same in the cerebellum of Tr mice and their corresponding controls. In contrast, there was no diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Copper concentration and SOD activity followed exactly the same pattern in brain capillaries, cerebrum, and cerebellum. A positive correlation between SOD activity and copper content has been reported previously by us and by other investigators (Bohnenkamp and Weser, 1977;Bettger et al, 1978;Paynter et al, 1979;Cloez et al, 1989), and in vivo studies have shown that a decrease in copper concentration is closely associated with decreased SOD activity (Mylroie et al, 1986). The activity of protective enzymes, therefore, may be limited by the availability of essential trace elements.…”
Section: Discussionsupporting
confidence: 77%
“…Copper concentration and SOD activity followed exactly the same pattern in brain capillaries, cerebrum, and cerebellum. A positive correlation between SOD activity and copper content has been reported previously by us and by other investigators (Bohnenkamp and Weser, 1977;Bettger et al, 1978;Paynter et al, 1979;Cloez et al, 1989), and in vivo studies have shown that a decrease in copper concentration is closely associated with decreased SOD activity (Mylroie et al, 1986). The activity of protective enzymes, therefore, may be limited by the availability of essential trace elements.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to brain, the PNS has rarely been examined for protection against peroxidation. It has been shown that sciatic nerve exhibits enzymatic defense against peroxidation in dogs (Chvapil et al, 1982) as well as in mice (Cloez et al, 1989) and contains measurable amounts of vitamin E (Vatassery et al, 1986;Gross-Sampson et al, 1988). It is interesting that in a neurological dysmyelinating mutant with an altered PNS, the trembler mouse, we found that enzymatic protection (Cloez et al, 1989) and vitamin E levels (Bourre et al, 1987a) are altered.…”
mentioning
confidence: 67%